Warsaw in the face of the Bolshevik invasion of 1920 - Załęczny, Jolanta (City and War, 2021)
Warsaw, although not directly the battlefield during the war of 1920, played an important role in it. The city was the seat of the most important institutions: the State Defense Council, the Civic Executive Committee for State Defense, and above all, the base for military and provisioning activities. As usual, the capital’s community did not disappoint. More volunteers came to the recruitment points for the Volunteer Army, scouts came on the order of General Haller. The inhabitants of the capital organized help for the fighters, hospitals worked intensively. The street in Warsaw was a place of agitation and propaganda. This was the purpose of posters and appeals. Funerals of the fallen in the battles with the Bolsheviks became patriotic manifestations. All activities were widely reported in the Warsaw press, commented on by residents and observers of the events in the diaries, and in retrospect – in the memoirs. The analysis of various sources allows for an interesting picture of the capital to be drawn during the military operations of 1920.